Prediction of the course of antibiotic-associated diarrhea caused by Clostridioides difficile based on clinical and laboratory characteristics of the disease - Konstantin D. Ermolenko; Tatiana V. Potapova; Kseniia V. Silav; Konstantin V. Zhdanov; Dmitry A. Lioznov; Denis A. Gusev (Терапевтический архив)
Background. The most severe complications of antibiotic use are clostridial infection (CDI) and pseudomembranous colitis (PMC). There is a need for further study of these conditions and identification of their triggers.